2017
DOI: 10.15414/jmbfs.2017/18.7.3.275-280
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Sensory Characteristics of Chicken Breast Meat After Dietary Supplementation With Probiotic Given in Combination With Bee Pollen and Propolis

Abstract: The present study evaluated the effect of probiotic in combination with bee pollen and propolis in diet of broilers on chemical and sensory characteristics of chicken breast meat. A total of 180 one-d-old chicks of mixed sex were randomly assigned to three dietary groups as follows: 1. control group (C); 2. basal diet supplemented with 400 mg bee pollen (ethanol extract) per 1 kg of feed and 3.3 g probiotic (Lactobacillus fermentum) per day in water (E1); 3. basal diet supplemented with 400 mg propolis (ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Breast muscles of Muscovy ducks with the lowest fat content received the lowest scores for tenderness, juiciness, and aroma, which was not confirmed in our study. Conversely, Trembecká et al (2017) reported the lowest scores for juiciness, tenderness, taste, and aroma of breast muscles from 42 d old Ross 308 broilers with the highest fat content. Baéza et al (1998) stated lower juiciness and tenderness of breast meat from female compared to male Muscovy ducks, which is in agreement with our findings for this duck genotype.…”
Section: Meat Sensory Propertiesmentioning
confidence: 90%
“…Breast muscles of Muscovy ducks with the lowest fat content received the lowest scores for tenderness, juiciness, and aroma, which was not confirmed in our study. Conversely, Trembecká et al (2017) reported the lowest scores for juiciness, tenderness, taste, and aroma of breast muscles from 42 d old Ross 308 broilers with the highest fat content. Baéza et al (1998) stated lower juiciness and tenderness of breast meat from female compared to male Muscovy ducks, which is in agreement with our findings for this duck genotype.…”
Section: Meat Sensory Propertiesmentioning
confidence: 90%
“…In contrary with this study, Istiqomah et al (2013) reported that broilers fed probiotic (multi culture, 10 12 cfu/g) produced meat with lower cholesterol content (58.40 mg/100 g) than control (85.74 mg/100 g). Trembecká et al (2020) also stated that the breast meat of chickens fed with propolis and probiotic (L. fermentum) had the lowest cholesterol content (77.94 mg/100 g) compare than other treatments (87.06 and 90.14 mg/100 g).…”
Section: Cholesterol Content In Egg and Meatmentioning
confidence: 97%
“…The dietary addition of bee pollen in the concentration of 400 mg/kg have improved the amino acid profile of breast and thigh muscles, with significantly increased concentrations of tyrosine in the breast and significantly decreased concentrations of proline in breast and thigh muscles, respectively [131]. Trembecká et al [132] have investigated the influence of bee pollen on the chemical and sensory characteristics of chicken breast meat. Results have shown that diet did not affect the chemical characteristics of chicken meat, except for supplementation with bee pollen and probiotics, which resulted in increased fat content.…”
Section: Bee Pollenmentioning
confidence: 99%